PENGARUH MANAJEMEN MODAL KERJA, LIKUIDITAS, LEVERAGE, UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PERUSAHAAN (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Pada Tahun 2012-2015) - Puguh Adi Setiawan, 13.05.52.0060; Poerwati, Rr. Tjahjaning (Students' Journal of Accounting and Banking, 2017)
This study examined the effect of the effect of working capital management. liquidity, leverage, company size and sales growth to profitability. The study was conducted on companies listed in the Bursa Efek Indonesia. The sampling method using purposive sampling with a period of 2012 to 2015. The relationship between variables influence is described using multiple regression analysis. The results showed that the average collection period, average payment period, and the size of the company's significant positive effect on profitability. Average day's inventory, and leverage significant negative effect on profitability. While likuidity and sales growth showed a negative result no significant effect on profitability.Keywords: Working Capital Management, Liquidity, Leverage, Firm Size, Growth, Profitability, ROA